Motivations of Retailers Accepting Cryptocurrency Payments and Their Implications on Retail Customer Experience - Muhammed Ali Yetgin; Kasım Yılmaz; Volkan Temizkan (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
The level of technology use of humanity has increased, while the interest in digital assets has increased with the effect of the pandemic period. This increasing interest has led to curiosity about what kind of consumer experience cryptocurrencies will offer when used in retail shopping. This study aims to reveal the advantages and disadvantages of using cryptocurrencies in shopping based on the experiences of businesses that accept payments with cryptocurrencies. Interviews were conducted with 9 businesses in Turkey that accept payments with crypto money using the in-depth interview technique in this study. As a result of the content analysis carried out with the NVivo analysis program for the findings, a research model was proposed. The results of this research point out that crypto currencies are preferred by consumers and retailers due to the fact that they are a fast, safe and cheap global payment tool. However, it has been found that there are also consumers who are totally unaware of the existence of payments with crypto currencies. Some consumers do not prefer payments with crypto currencies either because of low technology usage level or lack of trust to the system. However, when necessary legal sub-regulations are made and everything is digitized, money will also become digital in the common opinion. Unlike the studies in the literature, as a result of this study, it is predicted that payments with crypto money will be one of the alternative payment tools of the future, after the cryptocurrencies are positioned on a legal platform by the official authorities.